Beef quality assurance schemes: Can they improve farm economic performance?. Issue 3 (30th December 2020) - Tsakiridis, Andreas; Wallace, Michael; Breen, James; O'Donoghue, Cathal; Hanrahan, Kevin
Abstract: Beef quality assurance initiatives have been developed to assure consumers of the quality and safety of supplied beef, as well as the environmental‐orientation of farm production practices. However, the potential economic benefits of quality schemes to European beef cattle farmers have been overlooked. This paper uses farm‐level data to identify the drivers of Irish farmers' participation in Bord Bia's Beef and Lamb Quality Assurance Scheme (BLQAS) in 2012, and assesses the impact of participation on farm gross margins. After controlling for potential self‐selection bias, we cannot find reliable evidence that the gross margins of participants in beef quality assurance schemes have been affected by their decision to participate. Consequently, lack of financial incentives can be a barrier to farmer participation in beef quality assurance schemes [EconLit citations: L25, M21, Q12].